ORGANIZATIONAL PROJECTION IN THE EDUCATIONAL FIELD IN THE CONTEXT OF EDUCATIONAL CHANGE MANAGEMENT: THEORETICAL ANALYSIS - Semenets-Orlova I.A. (Pressing Problems of Public Administration, 2015)
The article is dedicated to conceptualization of the organizational projection as a method of an activity related to educational change management. The author has detected peculiarities of staged building an organizational project. The article determined the functional load and opportunities of application of the organizational projection within a system of educational change public administration.